RANCANG BANGUN SISTEM INFORMASI PENGELOLAAN DOKUMEN TANGIBLE CULTURAL HERITAGE - Khafiizh Hastuti; Abu Salam; Budi Handoko; Erwin Yudi Hidayat (Semantik, 2014)
The geographical position of Central Java Â which Â is Â in Â the middle of Â the island of Â Java,making it aÂ â€œmeltingpotâ€of cultures Â as well Â as the Â cultural center Â of Java Â island. Â Cultural Â heritage Â is dividedinto Â tangible Â cultural Â heritage Â and Â intangible Â cultural heritage. Â Tangible Â cultural heritage Â is Â theÂ work of Â the human Â body Â that Â can Â be moved Â or Â moving, Â or Â that Â cannot Â be moved Â or Â did not Â move.Department of Culture Â and Â  Â Tourism of Â Central Â Java has documented Â manually Â cultural Â heritagebut very vulnerable to damage. There are also many cultural Â heritages that have not been recorded.Â The process of data collection and recording are very difficult, since the datasources are scatteredand Â not well organized. Â Documentation Â of cultural heritage Â in Central Java Â can Â be used Â as Â aÂ information Â  Â system Â database Â fora wide range of Â cultura Â linterests Â in Â Central Java. Â The aim is tofacilitate Â and Â ease Â The Â Department of Â Culture Â and Tourism of Â Central Â Java Â to Â documents andÂ records cultural heritage collections for the category of tangible cultural heritage. In the long-termÂ plan, this system can be used Â as a reference by another region, thus forming the Â national culturalÂ heritage documentation system.